The Glutamate Receptor-Like Protein GLR3.7 Interacts With 14-3-3ω and Participates in Salt Stress Response in Arabidopsis thaliana - Wang, Po-Hsun; Lee, Cheng-En; Lin, Yi-Sin; Lee, Man-Hsuan; Chen, Pei-Yuan; Chang, Hui-Chun; Chang, Ing-Feng (Frontiers in Plant Science, 2019)
Ionotropic glutamate receptors (iGluRs) are ligand-gated cation channels that mediate fast excitatory neurotransmission in the mammalian central nervous system. In the model plant Arabidopsis thaliana, a family of 20 glutamate receptor-like proteins (GLRs) shares similarities to animal iGluRs in sequence and predicted secondary structure. However, the function of GLRs in plants is little known. In the present study, a serine site (Ser-860) of AtGLR3.7 phosphorylated by a calcium-dependent protein kinase (CDPK) was identified and confirmed by an in vitro kinase assay. Using a bimolecular fluorescence complementation and quartz crystal microbalance analyses, the physical interaction between AtGLR3.7 and the 14-3-3ω protein was confirmed. The mutation of Ser-860 to alanine abolished this interaction, indicating that Ser-860 is the 14-3-3ω binding site of AtGLR3.7. Compared with wild type, seed germination of the glr3.7-2 mutant was more sensitive to salt stress. However, the primary root growth of GLR3.7-S860A overexpression lines was less sensitive to salt stress than that of the wild type line. In addition, the increase of cytosolic calcium ion concentration by salt stress was significantly lower in the glr3.7-2 mutant line than in the wild type line. Moreover, association of 14-3-3 proteins to microsomal fractions was less in GLR3.7-S860A overexpression lines than in GLR3.7 overexpresion line under 150 mM NaCl salt stress condition. Overall, our results indicated that GLR3.7 is involved in salt stress response in A. thaliana by affecting calcium signaling.